Infectious Spleen and Kidney Necrosis Virus Triggers Ferroptosis in CPB Cells to Enhance Virus Replication - Qiushuang Zhang; Ouqin Chang; Qiang Lin; Hongru Liang; Yinjie Niu; Xia Luo; Baofu Ma; Ningqiu Li; Xiaozhe Fu (Viruses)
The role of ferroptosis—a novel iron-dependent programmed cell death pathway—in infectious spleen and kidney necrosis virus (ISKNV) infection remains poorly understood. Here, we demonstrate that ISKNV infection induces ferroptosis in CPB cells. Following ISKNV challenge, CPB cells exhibited hallmark morphological alterations including mitochondrial shrinkage, increased membrane density, and cristae reduction. Biochemical assays confirmed significant time-dependent elevations in ferroptosis markers: malondialdehyde (MDA, 1.7-fold), reactive oxygen species (ROS, 3.14-fold), and ferrous iron (Fe2+, 1.42-fold) compared to controls (p < 0.05). Mechanistic studies revealed that ISKNV downregulated glutathione peroxidase 4 (GPx4) while upregulating acyl-CoA synthetase long-chain family member 4 (ACSL4), as validated by quantitative real-time PCR (qRT-PCR) and immunoblotting. Ferroptosis induction with erastin enhanced ISKNV replication, whereas inhibition with liproxstatin-1 suppressed viral yield. These findings establish that ISKNV exploits ferroptosis to facilitate its replication, and pharmacological blockade of this pathway significantly suppresses viral propagation, providing a new strategy and intervention approach for controlling ISKNV infection.